2003
DOI: 10.3346/jkms.2003.18.6.849
|View full text |Cite
|
Sign up to set email alerts
|

The Prophylactic Use of Lamivudine Can Maintain Dose-Intensity of Adriamycin in Hepatitis-B Surface Antigen (HBs Ag)-positive Patients with Non-Hodgkin's Lymphoma Who Receive Cytotoxic Chemotherapy

Abstract: 2/week (55% RDI) in Groups B (p<0.001). Our data suggest that the frequency of chemotherapy-related HBV reactivation may be significantly decreased by lamivudine prophylaxis with maintenance of the dosage of adriamycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 30 publications
1
32
1
1
Order By: Relevance
“…This will lead to the development of lamivudine resistance caused by point mutations, with substitution of either valine or isoleucine for the amino acid position 204 methionine (rtM204V or rtM204I, respectively) in the HBV DNA polymerase gene (tyrosinemethionine-aspartate-aspartate [YMDD] motif) [67]. Its risk increases as the therapy is prolonged, reaching a level of 67% after 4 years in nonimmunocompromised patients Jang et al 88 Lim et al 127 Yeo et al 119 Lee et al 118 Idilman et al 117 Yeo et al 116 Leaw et al 115 Ozguroglu et al 114 Lau et al 85 Persico et al 113 Shibolet et al 112 Dai et al 111 Nagamatue et al 58 0.001 0.01 0.1 1 10 100 1000…”
Section: Preemptive Use Of Nucleoside Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…This will lead to the development of lamivudine resistance caused by point mutations, with substitution of either valine or isoleucine for the amino acid position 204 methionine (rtM204V or rtM204I, respectively) in the HBV DNA polymerase gene (tyrosinemethionine-aspartate-aspartate [YMDD] motif) [67]. Its risk increases as the therapy is prolonged, reaching a level of 67% after 4 years in nonimmunocompromised patients Jang et al 88 Lim et al 127 Yeo et al 119 Lee et al 118 Idilman et al 117 Yeo et al 116 Leaw et al 115 Ozguroglu et al 114 Lau et al 85 Persico et al 113 Shibolet et al 112 Dai et al 111 Nagamatue et al 58 0.001 0.01 0.1 1 10 100 1000…”
Section: Preemptive Use Of Nucleoside Analoguesmentioning
confidence: 99%
“…On the other hand, prolonged therapy with nucleos(t)ide analogues is associated with an increased likelihood of developing lamivudine-resistant mutants. Hence, most cancer centers would aim at discontinuing or withdrawing preemptive lamivudine as soon as possible to limit the duration of antiviral therapy [57,85,86,[111][112][113][114][115][116][117][118][119]127]. However, at the moment there is no available consensus on the optimal duration of lamivudine therapy.…”
Section: Preemptive Use Of Nucleoside Analoguesmentioning
confidence: 99%
“…Recent studies have shown that prophylaxis with lamivudine before the initiation of chemotherapy reduces both the incidence and severity of HBV reactivations. [12][13][14][15][16][17][19][20][21][22][23][24][25][26] However, no studies have investigated the use of prophylactic lamivudine in an economic analysis. In this study, we compared the costs and clinical outcomes of 2 different strategies for chronic hepatitis B carriers undergoing chemotherapy for lymphoma treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Data from 14 studies published from various parts of the world between 1990 and 2006 that examined HBV reactivation in lymphoma patients undergoing chemotherapy were collected (Table 1). [12][13][14][15][16][17][19][20][21][22][23][24][25][26] Seven of these studies compared the prophylactic use of lamivudine during chemotherapy to the empiric use of the drug, [12][13][14][15][16][17]26 6 studies restricted lamivudine to the treatment of reactivation, [20][21][22][23][24][25] and 1 study examined only the prophylactic use of lamivudine. 19 Lymphoma and Chemotherapy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation